2019
DOI: 10.1038/s41598-019-46888-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of intravenous immunoglobulin therapy in the survival rate of pediatric patients with acute myocarditis: A systematic review and meta-analysis

Abstract: The treatment of pediatric myocarditis is controversial, and the benefits of intravenous immunoglobulin (IVIG) are inconclusive due to limited data. We searched studies from PubMed, MEDLINE, Embase, and Cochrane Library databases since establishment until October 1st, 2018. Thirteen studies met the inclusion criteria. We included a total of 812 patients with IVIG treatment and 592 patients without IVIG treatment. The meta-analysis showed that the survival rate in the IVIG group was higher than that in the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Evidence for the use of IVIG and glucocorticoids to treat MIS‐C is also based on the use of these treatments in patients with KD and fulminant myocarditis, both of which are conditions that resemble MIS‐C in some aspects. IVIG at a dose of 2 gm/kg prevents CAAs in KD, while the benefit of IVIG in myocarditis remains unclear; however, case reports of successful use of IVIG in coronavirus‐associated myocarditis have been published (22,32,34–40). Before IVIG is given, cardiac function and fluid status should be assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the use of IVIG and glucocorticoids to treat MIS‐C is also based on the use of these treatments in patients with KD and fulminant myocarditis, both of which are conditions that resemble MIS‐C in some aspects. IVIG at a dose of 2 gm/kg prevents CAAs in KD, while the benefit of IVIG in myocarditis remains unclear; however, case reports of successful use of IVIG in coronavirus‐associated myocarditis have been published (22,32,34–40). Before IVIG is given, cardiac function and fluid status should be assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetrical funnel plot showed in gure 7a and P=0.001 <0.05 for Egger , s test demonstrated that our studies existed publication bias for OS ( gure 8a).While statistical tests showed no publication bias for RFS/DFS was found in our study(P=0.93>0.05 for Egger , s test and p=0.048 for Begg , s test), gure 8b.Then,trim-and-ll method was conducted to adjust funnel plots [20,21].As evidenced in gure 9,four missing studies were added in analysis of OS.The recalculated results were still signi cant for OS,the HR was 1.39 (95%CI:1.11-1.75),indicating the conclusions in our meta-analysis were stable and reliable.…”
Section: Resultsmentioning
confidence: 84%
“…There are only a few prospective blinded randomized trials that have specifically targeted viral infections or the associated inflammatory cascades in myocarditis. Presently, evidence does not support the routine use of corticosteroids or intravenous immunoglobulin alone [32,33], although combined treatment of corticosteroids with immunosuppressants has shown non-significant increases in LVEF [32]. The use of extracorporeal membrane oxygenation, however, has been shown to provide favorable outcomes for patients with myocarditis and sepsis [34], as well as fulminant myocarditis [35].…”
Section: Discussionmentioning
confidence: 99%